The Fund's Income Position For FY 2020 : Actual Outcome. (Policy Papers; Policy Paper, 2020)
This paper reports on the Fund's income position for FY 2020 following the closing of the Fund's accounts for the financial year and completion of the external audit. Net operational income was about SDR 1.4 billion, slightly higher than estimated in the April supplement, mainly reflecting higher investment income. However, the unrealized pension-related adjustment in FY 2020, stemming mainly from the actuarial remeasurement of staff retirement plan assets and liabilities, was larger than previously estimated and more than offset the Fund's net operational income, contributing to an overall net loss of about SDR 1.4 billion for the year.